Growth mechanism and electrical properties of tungsten films deposited by plasma-enhanced atomic layer deposition with chloride and metal organic precursors - Lee, Yujin; Seo, Seunggi; Nam, Taewook; Lee, Hyunho; Yoon, Hwi; Sun, Sangkyu; Oh, Il Kwon; Lee, Sanghun; Shong, Bonggeun; Seo, Jin Hyung; Seok, Jang Hyeon; Kim, Hyungjun (Applied Surface Science, 2021)
We compared the growth characteristics and film properties of tungsten (W) thin films prepared by atomic layer deposition (ALD) using two newly synthesized precursors, tungsten pentachloride (WCl5) and ethylcyclopentadienyltungsten(V) tricarbonyl hydride (HEtCpW(CO)3), with Ar/H2 plasma as the reactant. The purpose of this study was to evaluate the suitability of these precursors for W thin films used in interconnect technology. The growth characteristics and film properties were significantly affected by the ligands of the precursors. The chemical compositional analysis results showed that high-purity thin films were obtained using the WCl5 precursor, compared to the films obtained using the HEtCpW(CO)3 precursor, which were relatively high in carbon content and oxygen impurities. The W thin films obtained from the WCl5 precursor showed superior electrical properties compared to those of the HEtCpW(CO)3 precursor, which were related to the crystallinity and film density in addition to the impurities. These results provide profitable information regarding the selection of a pertinent precursor for the device fabrication.
Keywords: Atomic-layer deposition; Characteristic properties; Density-functional-theory; Films properties; Growth characteristic; Halide; Metal organic; Precursor; Property; Thin-films; Atomic layer deposition; Density functional theory; Halide; Metal organic; Precursor; Tungsten